A formação do agir crítico-reflexivo nas aulas de filosofia - Santos, Teresa D'Angelo (2011)
The aim of this research is to critically understand how the argumentation and the performances in the Philosophy classes can create basis to a critical-reflective act in the world, from the production of shared meanings. The study is developed in the context of Applied Linguistics and is inserted in the Social-Historical Cultural Activity (TASHC), discussed by Vygotsky and his collaborator Leontiev, when they showed the importance of language as a constitutive source of social activity and consciousness. The same way, theoretical basis is searched in the discussions on senses and meaning developed by Vygotsky, and afterwards, complemented by Cole, Newman and Holzman among other authors and followers. Based on the relevance and the comprehension of the space importance to Philosophy classes as a reference to the constitution of a critical-reflective act, there is an attempt to highlight the knowledge production and reframing through the interconnection of individual senses and the shared meanings in a creative way, according to Liberali s studies. It refers to a critical research on collaboration, in Magalhães conception, which focus is to know, observe, and transform to enable possible interventions in the Philosophy class practice, contributing with references in the students and teachers argumentative production, but also creating opportunities to a critical citizenship act in the world. The school context to be analyzed is of a private school located in the west part of the city of São Paulo. The data was produced and collected by audio and video recording of the classes, from which three lessons were selected to constitute the corpus of analysis. The interpretation and analysis categories were organized based on Pontecorvo, Orsolini, Sanchez-Vasquez, Lobman and Lundquist. The results reinforce the importance of the production of references to the abilities of argumentative language and the development of students critical-reflective act in their daily and academic activities, as to contribute to the creation of an educational practice that focus on an education towards citizenship